PENGARUH STRATEGI DIFERENSIASI TERHADAP KEPUASAN KONSUMEN HOTEL JATRA PEKANBARU - Rahmi, Raisa; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Differentiation strategy is a strategy that saw that the resulting product has a differentand unique compared to other similar products . The stages of differentiation strategyin this stage is the differentiation of products / services , image differentiation anddifferentiation of personnel . Customer satisfaction is the level of consumer feelingafter using a product if the product has met what diharakannya . Where the customersatisfaction is considered there are five aspects , namely the reliability of the hotel ,the hotel responsiveness , assurance given to the employees of the hotel , the hotelstaff 's attention to hotel guests and physical appearance .Grand Jatra Hotel Pekanbaru is the accommodation establishments locatedin Pekanbaru , where this hotel is a five-star hotel . The hotel is located center of thecity and within easy reach of entertainment and spending . As hotels classified infive-star hotel , the Hotel Grand Jatra Hotel Pekanbaru is adequate with a strategiclocation that is in the city center , has interesting buildings and facilities - fsilitasfairly complete. Based on the analysis of this study showed that the differentiationstrategy has a positive influence on consumer kepuasn Jatra Hotel Pekanbaru . HiThis can be seen from the analysis are known from the t ( 39.480 ) > t table ( 3.920 )and sig ( 0,000 ) < 0.05 . So the hypothesis that there is a differentiation strategy toinfluence consumer satisfaction can be accepted .Keywords : Differentiation Strategy , Customer Satisfaction